Effects of carbohydrate mouth rinse and caffeine on high-intensity interval running in a fed state - Devenney, S.; Mangan, S.; Shortall, M.; Collins, K. (Applied Physiology, Nutrition, and Metabolism, 2018)
The current study aims to identify if mouth rinsing with a 6% carbohydrate mouth-rinse (CMR) solution and mouth rinsing and ingestion of caffeine (CMR+CAFF) can affect exercise performance during steady-state (SS) running and high-intensity intervals (HIIT) in comparison with a 0% control solution (PLA) when in a fed state. Eight recreationally trained males completed 3 trials (CMR, CMR+CAFF, and PLA) of 45 min SS running and an HIIT protocol (90% peak treadmill velocity) until fatigue in a double blinded, repeated-measures study. Participants ingested a capsule of either CAFF or PLA before and after SS. Participants received a 25-mL bolus of carbohydrate solution (CMR and CMR+CAFF trials) or taste-matched PLA (PLA trial) prior to HIIT protocol and after every second effort. Heart rate and lactate responses were recorded throughout the SS and HIIT protocol. CMR+CAFF was significantly different when compared with PLA (p = 0.001; Cohens d = 1.34) and CMR (p = 0.031; Cohens d = 0.87) in relation to distance covered before fatigue. Although there was no significant difference between CMR and PLA, there was a small benefit for CMR (p = 0.218; Cohens d = 0.46). Results indicate that CMR and ingestion of CAFF leads to improvements in performance during interval sessions while participants were in a fed state. These findings indicate that the regular use of CMR can decrease the risk of gastrointestinal distress reported by athletes, which can be applicable to athletes in a real-world setting.